Factors affecting effectiveness and safety of warfarin in pediatric patients - Sujarit, Alisara; Tungjitrungroj, Papavadee; Tunphanich, Chonlawan; Tiempathom, Chanya; La-orkhun, Vidhavas (Journal of Health Sciences and Wellness, 2023)
The objective of this study was to examine factors affecting effectiveness and safety of warfarin in pediatric patients. This retrospective descriptive study was conducted at King Chulalongkorn Memorial Hospital. The clinical and medication-related data of patients aged 1-18 years, receiving warfarin between January 2015 and December 2020 were collected. Data were analyzed by descriptive statistics and multiple logistic regression. A total of 102 pediatric patients, the result showed that pediatric patients who did not have any surgery during warfarin treatment have by 9.67 times the odds of having the percentage of Time in Therapeutic Range (%TTR) more than 65, compared to patients that have surgery by adjusted with gender, age, weight, drug-drug interactions and non-compliance (adjusted OR 9.67, p=0.037). Moreover, TTR is lower than the therapeutic target (median: 38.3; IQR: 21.4, 67.4). However, this study found thromboembolism only 2 patients and only one patients of major bleeding. In conclusion, surgery during warfarin treatment in pediatric patients is important factor that affects the percentage of Time in Therapeutic Range that may affects to effectiveness and safety of pediatric patients using warfarin.